Foreign Workers’ Roles for Businesses Breakout Process in an Ethnically Themed Market: The Case of Halal Food Markets in Kyoto, Japan - Aris Chandra Pradikta (Populasi, 2019)
This article focuses on understanding the connection between the breakout strategies of businesses and the migrant workers’ employment opportunities in ethnically themed markets, especially halal food businesses. Accordingly, this research aims to analyze the working sector where migrants are employed. On the one hand, globalized market conditions demand workers with adequate skills and knowledge to work abroad. On the other hand, studies in global cities describe that migrants’ working sector tends to serve economic areas that mainly assist similar ethnic customers. In order to address the issue of enclaving occupational activities, this research uses primary data obtained from ethnographic research and analyzes the findings using the existing frame of the breakout process and strategies. The research results show, first, the employment of foreign workers enables Japanese enterprises to reach targeted ethnic clientele by rebranding and remaking the existing products in the market. Moreover, even though these workers have been contributing to the companies’ breakout process, their roles cannot assure job security for the long-run. The evidence of this research also implies that in the current globalized market, labor importing practices rely on the dynamics of companies. However, as companies located in a specific location, the opportunity structures -such as local and national law, social discrimination, and market prospects- affect job stability along with migrants’ ability to transform their knowledge and skills.